SPECIFIC FEATURES OF TRANSLATING YOUTH SLANG FROM ENGLISH INTO UZBEK (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article examines the peculiarities and challenges of translating youth slang from English into Uzbek. Given that slang is a dynamic and culture-specific linguistic phenomenon, its translation requires a deep understanding of both source and target languages, as well as the sociocultural contexts. The paper analyzes various examples of contemporary English youth slang such as 'lit', 'ghost', 'salty', 'flex', and 'cringe', and explores the strategies used to find appropriate Uzbek equivalents. The study also discusses the limitations of literal translation and the necessity of employing descriptive and adaptive methods in rendering slang meaning accurately.